Nano-voids in epoxy resins: Role in the transport of light gases. (24th March 2017) - Roilo, David; Patil, Pushkar N.; Brusa, Roberto S.; Miotello, Antonio; Checchetto, Riccardo
Abstract: Epoxy membranes with same chemical structure but different free volumes were prepared using aliphatic epoxide and polyether diamines as cross-linking agents. Their fractional free volume f h ( T ) was previously evaluated as a function of temperature and cross-linking density [P. N. Patil et al., PhysChemChemPhys 18 (2016) 3817–3824]. Original H2 permeation measurements were performed changing sample temperature and network structure and compared with CO2 and N2 transport data. Modelling gas permeability Φ in the framework of the free volume theory we observe that the Arrhenius-type behavior of Φ for test gases is consequence of the f h ( T ) linear increase with temperature and that at equal f h value membranes exhibit increasing Φ values by decreasing the cross-linking density. Analysis of permeability data on this set of test molecules with different size and condensation properties suggests that increasing the cross-linking between polymer chains limits their thermal fluctuations and the redistribution of the free volume elements where diffusional jumps of penetrant molecules occur. Graphical abstract: Highlights: Epoxy polymers with different free volumes can be prepared changing cross-linker chain length. Arrhenius-type behavior of CO2, N2 and H2 permeability observed. CO2, N2 and H2 permeability depends on the cross-linking density. Linear increase of fractional free volume with temperature controls gas permeability. Cross-linking density controls free volume elements redistribution.